Comparisons of mapped magnetic field lines with the source path of the 7 April 1995 type III solar radio burst. Issue 7 (28th July 2016) - Li, B.; Cairns, Iver H.; Gosling, J. T.; Malaspina, D. M.; Neudegg, D.; Steward, G.; Lobzin, V. V.
Abstract: Ideally, the sources of type III solar radio bursts, which are produced mainly by flare‐accelerated electron beams, trace the magnetic field lines along which the beams propagate from the Sun to interplanetary space. A recently developed 2‐D approach for large‐scale mapping of magnetic field lines between the Sun and Earth in the solar equatorial plane is applied to the sources of the 7 April 1995 type III radio burst imaged by Ulysses and Wind. The approach uses near‐Earth solar wind data and a solar wind model with intrinsic nonradial magnetic field at the source surface of the solar wind. Quantitative agreement is found between the mapped field lines, the observed path of the radio source centroids, and the field configurations inferred from solar wind suprathermal electrons observed by Wind. Moreover, the mapped field lines are consistent with Wind not observing the in situ type III electron beam, Langmuir waves, and local radio emission for this type III event. Key Points: Large‐scale magnetic field lines are mapped in the solar equatorial plane for the 7 April 1995 type III solar radio burst Mapped field lines are consistent with the field configuration traced by the radio source centroids Mapped field lines are also consistent with observations of suprathermal and energetic electrons and waves